Assessment of Farmer’s Attitude and Social Vulnerability to Climate Change in the Semi-arid Region - D. C. Meena,; R. K. Dubey, Rama Pal, S. K. Dubey, Rajesh Bishnoi, (Indian Journal of Extension Education, 2022)
This study was conducted in the semi-arid region, Agra of Uttar Pradesh, during 2016-19 to assess farmers’ perceptions and attitudes about climate change and farmers’ social vulnerability; and identify the significant factors that influence social vulnerability. Primary data was collected from 120 farmers using a well-structured interview schedule. Results revealed that most respondents recognized the decline in the rainfall quantum and rise in temperatures and the increase in the frequency of hot days and droughts. Almost all respondents believed that soil and water conservation measures were most effective in mitigating the adverse effects of climate change. The social vulnerability index illustrated that more than half of respondents were moderate socially vulnerable in climate-changing scenarios. The multiple regressions results confirmed that land size, total income, perception, knowledge, awareness of climate change phenomena, and adaptive capacity were significant predictor variables for social vulnerability to climate change. There is a need to improve knowledge and perception and change attitudes among the respondents through an educational campaign, mass media exposure, and individual contact with trained extension personnel to effectively cope with the consequences of climate change.